MENINGKATKAN KEMAMPUAN PELAKU UMKM DI ERA DIGITALIASI MENGGUNAKAN LEARNING MANAGEMENT SYSTEM (LMS) DI PLUT KUMKM SUMATARA BARAT - Nurfiah, Nurfiah; Wahyudi, Wahyudi; Putri, Rahmi Eka; Derisma, Derisma; Satria, Budy; Khairi, Luthfil; Wijaya, Anggi Hadi; Dinilhak, Afdhal; Rahman, Arifan; Asti, Ajeng Dwi; Arifnur, Adi Arga; Sakinah, Putri; Syauqi, Muhammad Dawi; Putri, Sherly Ananda; Rahmi, Siti Fadhilah (Universitas Mataram, 2025)
PLUT KUMKM West Sumatra acts as a pioneer in supporting the development of MSMEs and Cooperatives through various services, including the field of human resources through training. Implementation of training that has limitations in reach and effectiveness. The main obstacle is the limited distance and time for MSME actors in remote areas and difficulty in monitoring and evaluating training. In the digitalization era, the application of Learning Management System (LMS) can be a solution to increase training flexibility and efficiency. This community service aims to develop LMS to facilitate training management, expand the reach of participants, and increase the effectiveness of training for MSMEs. LMS is designed using WordPress CMS with several additional plugins such as LMS tutors for material management, quizzes, and certificates, and WooCommerce plugins for participant registration management using a free coupon system. Development methods include needs analysis, system design, implementation, and trials. The LMS developed allows training to be carried out flexibly unlimited space and time as long as it has internet access, structured, and measurable. Features such as material management, online evaluation, and registration using coupons facilitate administration and increase the participation of MSME actors in all regions of West Sumatra. Utilization of LMS is effective in overcoming conventional training limitations because it does not have to be done face to face. By using LMS, PLUT KUMKM can expand the reach of training to regions, improve the quality of assistance, and support the acceleration of MSME digitalization in West Sumatra to develop, grow, and adapt in line with the development of the digital world.